1999
DOI: 10.1287/mksc.18.2.115
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Model to Forecast New Product Performance in Domestic and International Markets

Abstract: This paper attempts to shed light on the following research questions: When a firm introduces a new product (or service) how can it effectively use the different information sources available to generate reliable new product performance forecasts? How can the firm account for varying information availability at different stages of the new product launch and generate forecasts at each stage? We address these questions in the context of the sequential launches of motion pictures in international markets. Players… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0
13

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(195 citation statements)
references
References 34 publications
5
168
0
13
Order By: Relevance
“…Prag and Casavant (1994) found a negative relationship between the drama genre and revenue. Neelamegham and Chinatagunta (1999) used a Bayesian model to predict film attendance in domestic and international markets. They found that the thriller genre was most popular and romance was least popular.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prag and Casavant (1994) found a negative relationship between the drama genre and revenue. Neelamegham and Chinatagunta (1999) used a Bayesian model to predict film attendance in domestic and international markets. They found that the thriller genre was most popular and romance was least popular.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu, 2006). Neelamegham and Chintagunta (1999) focus on forecasting film performance in domestic and international markets.…”
Section: Forecastingmentioning
confidence: 99%
“…This early characterization of the market has stimulated many novel models, applicable to different problem areas including new movie attendance (Sawhney and Eliashberg, 1996;Neelamegham and Chintagunta, 1999).…”
Section: New-product Modelsmentioning
confidence: 99%